(untitled) (Itinera, 2019)
Theatre can be an important instrument of political and cultural resistance in difficult economical and social contexts, it can allow viewers to regain a sense of community. This issue, which arises from the international conference “Politiche del teatro” (held at the University of Milan on 28th and 29th November 2017, as a conclusion of the Creative Europe Project “Senses: The Sensory Theater”), aims to identify the specific forms that the political discourse assumes today in theatre and the aesthetic paradigms to which it refers.